Beyond the scaffold: alginate-based 3D biomaterials as a tool to investigate neuroinflammation - Coelho, Raquel Sousa (2024)
The incidence of neurodegenerative disorders of the central nervous system (CNS) is increasing worldwide, making them a leading cause of disability, particularly in aging populations. These diseases involve a progressive decline in neuronal function, often accompanied by neuroinflammation, that aims to protect and repair affected tissues but, when prolonged, can lead to neurotoxicity and exacerbate disease progression. Microglia, the CNS’s immune cells, are central to this process, releasing pro-inflammatory cytokines like TNF-a and IL-1β, which recruit astrocytes and trigger extensive remodeling of the extracellular matrix (ECM), as well as anti-inflammatory cytokines. Changes in ECM composition and mechanical properties that are observed in pathological scenarios, such as alteration in stiffness, further influence cell behavior and tissue homeostasis. Despite growing research, the interplay between microglia and ECM mechanics in the context of neuroinflammation remains unclear, with no studies in the literature using 3D in vitro models for exploring this topic. Therefore, this study explored how ECM mechanical properties affect microglial behavior, in the absence or presence of a neuroinflammatory stimulus, using a 3D tissue-engineered model that replicates key features of the brain ECM. Alginate hydrogels were prepared by mixing alginate solutions of varied oxidation status modified with RGD and PVGLIG peptides. The modification of the alginate backbone with the RGD peptide was chosen for its cell adhesion properties, while PVGLIG was used for its sensitivity to matrix metalloproteinases. Primary microglia cultures were established from postnatal day 1-2 Wistar Han rat pup cortices, and cells embedded within the hydrogels. The mechanical properties of hydrogels with and without encapsulated microglia were analyzed through rheology assays. Cell viability was studied using live-dead and resazurin assays, and cell morphology and proliferation was assessed through immunocytochemistry for F-actin and Ki- 67, respectively. A pro-inflammatory stimulus of lipopolysaccharide (LPS) was added to the culture and the resulting activation status was assessed by immunocytochemistry, quantitative real-time polymerase chain reaction (qRT-PCR) and measurement of nitrite production. In order to replicate the alterations in the ECM environment during neuroinflammation, the mechanical properties of the matrices were modified by adjusting the concentration of alginate and the degree of oxidation, leading to the production of three distinct formulations. Overall, we observed that the elastic modulus (G’) increased with higher alginate concentration (weight/volume; w/v) and lower levels of alginate oxidation. On the other hand, the viscous modulus (G’’) decreased when the alginate concentration (w/v) was doubled, and the oxidation degree was maintained but didn’t change when the oxidation degree was halved (while also doubling the alginate concentration). The complex modulus (G*) also increased with higher alginate concentration (w/v) and lower oxidation, which was mainly attributed to the significant increase in the elastic component. Rheological analysis of microglia-embedded hydrogels followed a similar pattern, yet showing consistently lower values for all measured parameters, suggesting a substantial impact of cells in the matrices’ mechanical properties. This impact is likely attributed not only to the mechanical properties of the cells themselves, but also to their influence during the crosslinking process. Live-dead assays confirmed over 60 % cell viability across all conditions. Metabolic activity and nitrite production increased in all formulations following LPS stimulation, with the softest condition showing the biggest increase. ICC assays revealed the difference in the morphology of the cells, through F-actin, and an increase in Ki-67 expression, upon LPS stimulation, with larger cell volumes observed in the formulations with a lower elastic modulus. Sphericity was highest in the formulation with the highest elastic modulus. YAP1, responsible for regulating cell growth, proliferation and apoptosis, showed an elevated expression and subcellular localization in the nuclei in the softest condition with LPS. RT-qPCR analysis showed increased expression of key inflammatory markers, including IL-6, NOS2, IL-10 and CD14, with CD14 being the most upregulated gene, especially in the presence of LPS. TLR4, a pathway for LPS to induce microglia activation, was downregulated in the matrices with higher alginate concentration (w/v), thus higher elastic modulus. Therefore, the softest formulation showed the highest gene expression response after LPS stimulation. These findings suggest a likely interplay between ECM mechanical properties and microglial function under LPS-induced activation, which aligns with the objectives of this project and the preconceived expectations. This work will contribute to the discovery of new therapeutic targets to tackle neuroinflammation and ultimately neurodegenerative diseases.